The madwoman in the cellar: trauma and gender after both World Wars : a field study of psychiatric files - Wernitznig, Dagmar; Justus Liebig University Giessen (My University, 2021)
By utilizing practical examples from the Abteilung für Psychatrie [psychiatric ward] at the Landeskrankenanstalt [province hospital] in Carinthia, Austria, in the wake of the two World Wars, this article seeks to explore the stories of hospitalized women and girls after armistices and peace treaties. Whereas the dialectics of conflict and resulting post-conflict traumas became increasingly accepted by medics for combat-ants during that time frame, this was not necessarily the case for comparable traumatic experiences of female civilians. Instead, for these patients, the Freudian definition of hysteria prevailed as a stereotypical feminine symptom. Accordingly, post-war tran-sitions from 1918 and 1945 onwards, with critical, sometimes even unstable, material and political infrastructures, consolidated a decidedly gender-related notion of trauma. This monopoly of trauma diagnoses, reserved for male patients, hence even resulted in misogyny towards institutionalized women, especially when they were refugees or displaced persons. As this study attempts to show, the mapping of mental illness or normality was heavily determined by sex, class, or ethnic background and in most instances served as an administrative tool for socio-political ends. The research for this contribution is based on archival work conducted for an ERC Advanced Grant, entitled EIRENE Post-War Transitions in Gendered Perspective: The Case of the North-Eastern Adriatic Region.
Keywords: Austria; civilians; gender; (post-)war trauma; psychiatry; ddc:300